Overcoming challenges in data collection: Gender in fish feed value chains in Bangladesh - Mamun-Ur-Rashid, M. (International Livestock Research Institute, 2016)
Mohammad Mamun-Ur-Rashid is a member of a research team that has tried to come up with a methodology to get information from women in Bangladesh. It’s not easy for women to speak up about unequal conditions or sexual harassment. It’s important to create an environment in which they are comfortable to talk. For example, it’s not easy to get the information from the big fish-millers, which are men. You need to engage with the right people to get the information. By creating more equal relations in the value chains, everyone will benefit. Interview with Mohammad Mamun-Ur-Rashid (WorldFish) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684